2008
DOI: 10.1007/s00535-008-2216-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of primary sclerosing cholangitis with onset age above 50 years

Abstract: Older PSC patients have higher IgE, possibly less association with UC, lower IgM, and a better prognosis. The pathogenesis of PSC may be different between older and younger patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 17 publications
0
16
5
Order By: Relevance
“…It has been reported that Japanese patients with PSC can be categorized into 2 groups [19,20], distinguished according to age at onset, but there seemed to be no association between the efficacy of bezafibrate and the age at onset in the present study. It is not clear from our study whether bezafibrate is useful for improving the prognosis of PSC, because the study was retrospective, the sample size was small, and the follow-up period was limited.…”
Section: Discussioncontrasting
confidence: 80%
“…It has been reported that Japanese patients with PSC can be categorized into 2 groups [19,20], distinguished according to age at onset, but there seemed to be no association between the efficacy of bezafibrate and the age at onset in the present study. It is not clear from our study whether bezafibrate is useful for improving the prognosis of PSC, because the study was retrospective, the sample size was small, and the follow-up period was limited.…”
Section: Discussioncontrasting
confidence: 80%
“…One of the most common laboratory findings is an increased IgM level in about 50% of patients. However, it has been reported that older patients do not present with this laboratory finding frequently; instead, a slightly elevated IgE level 6) and eosinophilia 7) is observed.…”
Section: Discussionmentioning
confidence: 87%
“…Among the characteristics described in older patients, there is an association between PSC and inflammatory bowel disease, particularly ulcerative colitis is present in 10% of older patients 6) compared to 90% in younger patients 1) . However, this association was not found in the present patient, suggesting that the disease has different pathophysiological mechanisms depending on the age of presentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PSC is frequently observed in males, Caucasians and Northern Europeans [38]; the incidence rate is 0.41–1.25 patients/100,000 person‐years [41, 42], and the mean age at onset is 42 years [38]. There are reports that the age distribution is bipolar in shape with one peak at the 20s and another peak between the 50s and 60s [43, 44]. It is classified into the following 4 stages: (1) small duct cholangitis, (2) progressive cholestasis, (3) cirrhosis, and (4) decompensation [38, 45].…”
Section: Primary Sclerosing Cholangitismentioning
confidence: 99%